Monitoreo continuo de glucosa durante la gestación en pacientes con diabetes mellitus tipo 2 pregestacional - del Mar Morales, María (2022)
Pregestational diabetes requires strict glycemic control during pregnancy.Continuous glucose monitoring (CGM) devices measure interstitial glucose levelswithout the need for capillary puncture. Four pregnant women with pregestationaltype 2 diabetes mellitus were studied with the aid of CGM during 2 weeks of theirgestation. They had weekly nutritional sessions and medical controls with anendocrinologist. The average glucose level ranged from 82 to 171 mg/dL. The CGMallowed early changes in the treatment of one patient with hypoglycemia. All patientsstated that the GCM helped them in their food selection. In conclusion, the GCMhelped in carbohydrate recognition and treatment readjustment. The CGM was wellaccepted for use.